Shifting mindsets: a realist synthesis of evidence from self‐management support training. Issue 3 (4th January 2018) - Davies, Freya; Wood, Fiona; Bullock, Alison; Wallace, Carolyn; Edwards, Adrian
Abstract : Context: Accompanying the growing expectation of patient self‐management is the need to ensure health care professionals (HCPs) have the required attitudes and skills to provide effective self‐management support (SMS). Results from existing training interventions for HCPs in SMS have been mixed and the evidence base is weaker for certain settings, including supporting people with progressive neurological conditions (PNCs). We set out to understand how training operates, and to identify barriers and facilitators to training designed to support shifts in attitudes amongst HCPs. Methods: We undertook a realist literature synthesis focused on: (i) the influence of how HCPs, teams and organisations view and adopt self‐management; and (ii) how SMS needs to be tailored for people with PNCs. A traditional database search strategy was used alongside citation tracking, grey literature searching and stakeholder recommendations. We supplemented PNC‐specific literature with data from other long‐term conditions. Key informant interviews and stakeholder advisory group meetings informed the synthesis process. Realist context‐mechanism‐outcome configurations were generated and mapped onto the stages described in Mezirow's Transformative Learning Theory. Results: Forty‐four original articles were included (19 relating to PNCs), from which seven refined theories were developed. The theories identified important training elements (evidence provision, building skills and confidence, facilitating reflection and generating empathy). The significant influence of workplace factors as possible barriers or facilitators was highlighted. Embracing SMS often required challenging traditional professional role boundaries. Conclusion: The integration of SMS into routine care is not an automatic outcome from training. A transformative learning process is often required to trigger the necessary mindset shift. Training should focus on how individual HCPs define and value SMS and how their work context (patient group and organisational constraints) influences this process. Proactively addressing potential contextual barriers may facilitate implementation. These findings could be applied to other types of training designed to shift attitudes amongst HCPs. Abstract : The authors show that a transformative learning process is often required to trigger the necessary mindset shift to allow integration of Self‐Management Support into routine care.